2018
DOI: 10.5539/ibr.v11n5p110
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Affecting Jordanians Housewives Consumption Behavior: A Qualitative Approach

Abstract: Based on the findings of semi-structured interviews with (N=129) Jordanian housewives, this study examined the psychological, social, and marketing influences on the purchase and consumption behavior of Jordanian housewives. Overall, the findings of this study showed that the purchase decisions of the housewives were motivated by necessity to satisfy basic needs and the family appeared to be the main influencer affecting the housewife purchase decision. With regards to the factors prohibiting consumption, infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…A tentative conclusion can be drawn that egg food is still the main mainstay for households to fulfillment animal protein needs from livestock. In accordance with the opinion of Obeidat et al (2018) that the purchase decisions of the housewives were motivated by the necessity to satisfy basic needs and the family appeared to be the main influencer affecting the housewife purchase decision.…”
Section: Characteristics Of Consumer and Households Expenditurementioning
confidence: 54%
See 1 more Smart Citation
“…A tentative conclusion can be drawn that egg food is still the main mainstay for households to fulfillment animal protein needs from livestock. In accordance with the opinion of Obeidat et al (2018) that the purchase decisions of the housewives were motivated by the necessity to satisfy basic needs and the family appeared to be the main influencer affecting the housewife purchase decision.…”
Section: Characteristics Of Consumer and Households Expenditurementioning
confidence: 54%
“…This means that meat and dairy for households are seen as luxury goods rather than eggs and conversely the eggs tend as goods inferior to other commodities. With regards to the social factors influencing the purchasing decision of housewives, the family was found to mainly influence the purchases of the housewives followed by the social class the consumer supposedly belongs to (Obeidat et al, 2018).…”
Section: Characteristics Of Consumer and Households Expenditurementioning
confidence: 99%
“…The study concluded that the factors that affect impulsive buying are discounts, promotion through social media, Facebook and Instagram, and the nature of hedonic shopping so that M98 Shop Jamik Bengkulu consumers prioritize wants over needs. Obeidat et al (2018) identified the factors that most influence purchasing and consumption in families in Jordan. The study concluded that meeting household needs and following them is the main influence behind Jordan homemakers' purchasing and consumption decisions.…”
Section: Previous Researchmentioning
confidence: 99%
“…Previous studies have focused on studying the consumption behavior of millennial students (Lestari, 2020), farmer consumption behavior (Haslina, 2018), family consumption behavior (Obeidat et al, 2018), consumption behavior of sharia hotel choices (Idris & Razali, 2016), and fast food consumption behavior (Wong et al, 2020). In contrast to other consumption behavior studies (Haslina, 2018;Idris & Razali, 2016;Lestari, 2020;Obeidat et al, 2018;Ruslani, 2019;Wong et al, 2020), this consumption behavior study targets the consumptive behavior of millennial mothers in cities near fishing areas using the consumption theory of Islamic economic thinker Imam Ghazali. This study is expected to be able to fill the gap of previous consumption behavior studies that have not used the theory of Islamic economic thinkers before.…”
Section: Previous Researchmentioning
confidence: 99%